2015
DOI: 10.1002/jaba.233
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing transition times in elementary school classrooms: Using computer‐assisted instruction to automate intervention components

Abstract: Research suggests that students spend a substantial amount of time transitioning between classroom activities, which may reduce time spent academically engaged. This study used an ABAB design to evaluate the effects of a computer-assisted intervention that automated intervention components previously shown to decrease transition times. We examined the effects of the intervention on the latency to on-task behavior of 4 students in 2 classrooms. Data also were collected on students' on-task behavior during activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
3
16
0
1
Order By: Relevance
“…Two students (Stephen and William) were subsequently exposed to self-monitoring, and increased on-task behaviors were observed for William only. These results replicate and extend previous research using mindfulness (Wilson & Dixon, 2010), as well as other research on similar behavioral interventions (Hine, Ardoin, & Foster, 2015;Lee et al, 1999) and self-monitoring protocols (e.g., Ninness, Fuerst, Rutherford, & Glenn, 1991). These results also highlight the clinical utility of the effects of mindfulness exercises paired with behavioral interventions, and suggest an additive effect between these interventions.…”
Section: Discussionsupporting
confidence: 87%
“…Two students (Stephen and William) were subsequently exposed to self-monitoring, and increased on-task behaviors were observed for William only. These results replicate and extend previous research using mindfulness (Wilson & Dixon, 2010), as well as other research on similar behavioral interventions (Hine, Ardoin, & Foster, 2015;Lee et al, 1999) and self-monitoring protocols (e.g., Ninness, Fuerst, Rutherford, & Glenn, 1991). These results also highlight the clinical utility of the effects of mindfulness exercises paired with behavioral interventions, and suggest an additive effect between these interventions.…”
Section: Discussionsupporting
confidence: 87%
“…Although Campbell and Skinner's (2004) evaluation did not control for any threats to internal validity, it did have heuristic value and influenced other researchers who evaluated the TTG using procedures that allowed them to draw cause-and-effect conclusions (Hawkins et al, 2015;Hine et al, 2015;Yarbrough et al, 2004). Yarbrough et al (2004) used a withdrawal design to evaluate the TTG in a second-grade classroom.…”
Section: Timely Transitions Gamementioning
confidence: 99%
“…Since this initial study, numerous researchers have found evidence that interdependent group-oriented contingencies could be used to reduce inappropriate classroom behaviors (Bowman-Perrott, Burke, Zaini, Zhang, & Vannest, 2016;Flower, McKenna, Muething, Bryant, & Bryant, 2014;Stage & Quiroz, 1997). More recently, researchers used interdependent group-oriented contingencies to reduce hallway transition times (Campbell & Skinner, 2004;Hawkins, Haydon, Denune, Larkin, & Fite, 2015;Hine, Ardoin, & Foster, 2015;Yarbrough, Skinner, Lee, & Lemmons, 2004). Campbell and Skinner (2004) worked with a sixth-grade teacher to develop the Timely Transitions Game (TTG), which involved the application of interdependent group rewards with randomly selected criteria.…”
mentioning
confidence: 99%
“…Even experienced educators have difficulty managing student behavior during transitions (Codding & Smyth, 2008;Hine, Ardoin, & Foster, 2015). The CWS allows educators to consistently apply procedures designed to transition the class from one set of rules to another as it transitions from one activity to another .…”
mentioning
confidence: 99%